1995
DOI: 10.1007/s002770050113
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's disease developing after spontaneous remission of chronic lymphocytic leukemia

Abstract: We present a 71-year-old patient with chronic lymphocytic leukemia diagnosed 27 years ago. Initially, the disease was staged as Rai II and the patient suffered from secondary immunoglobulin deficiency. Nevertheless, no treatment was necessary at that time. Because of disease progression a single course of chemotherapy was given in 1984. During the following year there was a constant decline of the WBC, accompanied by normalization of the immunoglobulins; both have remained stable ever since that time. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Our ®ndings suggest the existence of a patient with T-PLL with an indolent course and spontaneous remission. Spontaneous remissions have been seen infrequently in patients with chronic lymphocytic leukaemia or low-grade non-Hodgkin lymphomas (Han & Sokal, 1970) and, in some cases, they were associated with viral infection, smallpox vaccination or a second neoplasm (Han, 1987;Schmidt et al, 1995). We found no special circumstance while following our patient.…”
Section: Discussionmentioning
confidence: 45%
“…Our ®ndings suggest the existence of a patient with T-PLL with an indolent course and spontaneous remission. Spontaneous remissions have been seen infrequently in patients with chronic lymphocytic leukaemia or low-grade non-Hodgkin lymphomas (Han & Sokal, 1970) and, in some cases, they were associated with viral infection, smallpox vaccination or a second neoplasm (Han, 1987;Schmidt et al, 1995). We found no special circumstance while following our patient.…”
Section: Discussionmentioning
confidence: 45%
“…Twelve cases of spontaneous remission in CLL have been reported in the literature since 1970 (Schmidt et al , 1995; Bernard et al , 1999). Most of these cases showed a significant decrease in the blood lymphocyte count and, in a few cases, this was associated with blood or bone marrow remission.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature undertaken by Schmidt et al (1995), 37 CLL patients were reported as experiencing spontaneous remission. However, only 11 cases presented in the series were true spontaneous remissions (in the absence of any treatment thought to modify disease).…”
Section: Discussionmentioning
confidence: 99%
“…Complete remission in CLL has rarely been reported after chemotherapy; some cases after low doses of chlorambucil or prednisone, splenic irradiation or high‐dose chemotherapy with autologous or allogeneic stem cell transplantation. 14 cases of untreated CLL entering spontaneous remission have been published over the last three decades ( Schmidt et al , 1995 ; Ribera et al , 1987 ). Most of them showed only a decrease in peripheral lymphocyte count and in a few cases this was associated with blood or marrow cytological remission.…”
mentioning
confidence: 99%
“…Persistence of phenotypic and molecular marrow detection of leukaemic cells suggests that long‐lasting remission may be observed even in the context of minimal residual disease. According to Schmidt et al (1995 ), with a median follow‐up of 4.2 years, only one out of 12 patients relapsed 3 years after spontaneous remission. We suggest that repetitive infections might have contributed to clinical remission through an immunological effect, potentially initiated by endogenous cytokine overproduction.…”
mentioning
confidence: 99%